2023
DOI: 10.1097/olq.0000000000001821
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vaginal Microbial Community Dynamics in the Pathogenesis of Incident Bacterial Vaginosis, a Pilot Study

Abstract: Background Despite more than 60 years of research, the etiology of bacterial vaginosis (BV) remains controversial. In this pilot study, we used shotgun metagenomic sequencing to characterize vaginal microbial community changes before the development of incident BV (iBV). Methods A cohort of African American women with a baseline healthy vaginal microbiome (no Amsel criteria, Nugent score 0–3 with no Gardnerella vaginalis morphotypes) were followed for 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Nearly all women are colonized with Gardnerella spp., but approximately one-third of women of reproductive age develop BV ( 26 ). In the days preceding symptomatic BV, the number of Gardnerella cells greatly increases and the number of Lactobacillus cells plummets ( 10 ). Vaginal pH increases due to the loss of lactic acid production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all women are colonized with Gardnerella spp., but approximately one-third of women of reproductive age develop BV ( 26 ). In the days preceding symptomatic BV, the number of Gardnerella cells greatly increases and the number of Lactobacillus cells plummets ( 10 ). Vaginal pH increases due to the loss of lactic acid production.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with BV are predisposed to adverse pregnancy outcomes including amnionitis, postpartum endometritis, and premature delivery, the leading cause of neonatal mortality ( 8 , 9 ). It is hypothesized that Gardnerella serve as primary colonizers of the vaginal mucosa, and they increase in relative abundance 3–4 days prior to the onset of symptomatic BV ( 7 , 10 ). It is also thought that Gardnerella dampen the host immune response and establish the BV biofilm prerequisite to the arrival of secondary colonizers, such as Fannyhessea vaginae and Sneathia spp.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, while the use of relative abundances was sufficient to detect significant reductions of many BVAB and increases in Lactobacillus following successful MTZ treatment, the magnitude of the effects that these bacteria have on the genital environment are directly linked to their absolute abundances or burden, the quantification of which may be required to understand the relationship between the vaginal microbiota, genital environment, and chlamydial clearance. Future studies would benefit from the quantification of absolute abundances of dominant vaginal bacterial taxa or by inferring absolute abundances from total bacterial burden in combination with compositional data ( Tettamanti Boshier et al., 2020 ; Elnaggar et al., 2023a ; Elnaggar et al., 2023b ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it is unknown whether anaerobic bacteria cause the loss or displacement of Lactobacillus spp. but it is a proposed step in some FGTI etiologies such as BV [25]; other studies have found that Lactobacillus phages could also play a role [26,27]. Regardless, the loss or displacement of the protective lactic acid-producing lactobacilli encourages FGTI-associated bacteria, such as Prevotella spp., to colonize the vaginal epithelium [28,29].…”
Section: Introductionmentioning
confidence: 99%